Evaluation of lung function among the Indian elite female weightlifters - Adhikari, Snehunsu; Perla, Adilakshmi; Sayana, Suresh Babu; Tiwari, Mithilesh K.; Medabala, Tambi (International Journal of Research in Medical Sciences, 2017)
Background: Spirometry is an essential tool to evaluate lung function of health and disease. Adaptability of lung and chest among athletes can be assessed by lung function test (LFT). The quest of our study was to evaluate the lung function (LF) of highly trained Indian female weighting athletes, and intended to appraise the adaptation of LF among trained elite athletes. Methods: Top ranked Indian female professional weightlifters (study group, n=6) were recruited for this study. Three out of the six weightlifters were from top ten world ranking of 6th, 7th and 9th. Age matched controls (control group, n=6) were selected for this study. Maximum voluntary ventilation (MVV), vital capacity (VC), forced vital capacity (FVC), percentage of forced expiratory volume in first second (FEV1%) and ratio of forced expiratory volume in first second and forced vital capacity (FEV1/FVC%) have been evaluated as per the ATS/ERS guidelines. Results: Statistically higher significant values of VC and FVC were noted in study group, where as other values (MVV, FEV1% and FEV1/FVC%) found no significant difference between two groups. Conclusions: Power, strength and explosiveness of the skeletal muscles are vital domains in weightlifting sport. Weightlifting is such a sport doesn’t require much ventilatory efforts during training as well as competition. This study clueing that physiological adaptation/ improvement of the pulmonary function (PF) depends on the type of the sport being engaged by the athletes.